O processo do trabalho do serviço social na política de saúde na atenção básica com a população indígena Xerente no município de Tocantínia - Silva, Mayra Candido da (Universidade Federal do Tocantins, 2024)
This study aimed to analyze the contribution of the work of Social Workers who work with indigenous people, based on the literature in the field of Social Service, and as specific objectives: to characterize the theoretical-methodological particularities of Social Workers' work with the indigenous population. Xerente and verify the obstacles placed on this professional in relation to his work with him. It aims to answer the following guiding question: What are the contributions of the professional work of social workers to health policy in primary care with the Xerente indigenous people in Tocantínia? This is the product of exploratory research, which used a narrative-type bibliographic review. The data was collected from February to May 2024 and processed through selective and critical reading. The main finding of the research signals the invisibility of the debate on indigenous issues in the profession in addition to the incipience of literature in relation to the binomial Indigenous peoples and Social Work.